The effectiveness of brief mindfulness training in reducing test anxiety among high school students - Yuqi Sun; Kezhen Lv; Wenlan Xie; Yuzheng Wang (BMC Psychology)
Abstract Background For many high school students, test anxiety is a prevalent issue that adversely affects their exam performance. Previous research has explored the effectiveness of mindfulness training in alleviating test anxiety; however, the lack of real-life exam scenarios and lengthy training sessions has limited its application. This study examines the effects of a brief, five-day mindfulness training and immediate session on enhancing students’ mindfulness levels and reducing their test anxiety. Methods The participants were recruited and divided into an experimental group (n = 29) and a control group (n = 32). The experimental group underwent a daily eight-minute mindfulness training for five consecutive days, while the control group engaged in a passive waiting period. To assess changes in mindfulness levels and exam performance, two exams were administered before and after the five-day mindfulness intervention, accompanied by the completion of the Five Facet Mindfulness Questionnaire. To evaluate changes in test anxiety levels, the State Anxiety Inventory was filled out on days 1, 3, and 5 of the training. Results After five days of mindfulness training, the mindfulness group showed significant improvements in overall mindfulness levels (particularly in observing and describing skills), a significant reduction in test anxiety and notable improvements in exam performance. Furthermore, the effects on test anxiety were observed after just one training session. Conclusions The study demonstrates that a brief, five-day mindfulness training can significantly enhance mindfulness levels, reduce test anxiety, and improve exam performance in high school students. The positive effects on test anxiety were noticeable after a single session.